Structural differences of cell walls in earlywood and latewood of Pinus sylvestris and their contribution to biomass recalcitrance - Liszka, Aleksandra; Wightman, Raymond; Latowski, Dariusz; Bourdon, Matthieu; Krogh, Kristian B. R. M.; Pietrzykowski, Marcin; Lyczakowski, Jan J. (Frontiers in Plant Science, 2023)
Scots pine (Pinus sylvestris L.) is an evergreen coniferous tree with wide distribution and good growth performance in a range of habitats. Therefore, wood from P. sylvestris is produced in many managed forests and is frequently used in industry. Despite the importance of pine wood, we still do not fully understand its molecular structure what limits improvements in its processing. One of the basic features leading to variation in wood properties is the presence of earlywood and latewood which form annual growth rings. Here, we characterise biochemical traits that differentiate cell walls of earlywood and latewood in Scots pine. We discover that latewood is less recalcitrant to enzymatic digestion, with galactoglucomannan showing particularly pronounced difference in accessibility. Interestingly, characterisation of lignin reveals a higher proportion of coniferaldehydes in pine latewood and suggests the presence of a different linkage landscape in this wood type. With complementary analysis of wood polysaccharides this enabled us to propose the first detailed molecular model of earlywood and latewood and to conclude that the variation in lignin structure is likely the main determinant of differences in recalcitrance observed between the two wood types in pine. Our discoveries lay the foundation for improvements in industrial processes that use pine wood since we show clear pathways for increasing the efficiency of enzymatic processing of this renewable material. Our work will help guide future breeding of pine trees with desired timber properties and can help link molecular structure of softwood cell walls to function of the different types of xylem in conifers.